2018
DOI: 10.3390/ijerph15051001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lumbopelvic Movement and Muscle Recruitment Associated with Prolonged Deep Squatting: A Pilot Study

Abstract: This study examined the changes in spinal kinematics and muscle recruitment of the lumbopelvic region associated with prolonged squatting. Eight subjects with chronic nonspecific low back pain (LBP) and eight asymptomatic subjects (AS) performed squat-to-stand and reverse movements, before and immediately after 15 min deep-squatting. Within-group and between-group differences in lumbopelvic kinematics and electromyographic activity acquired in lumbar erector spinae (ES), gluteus maximus (GM), and vastus latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Deep squatting is a motion involving total body flexion that can be used to evaluate functional movement [ 1 , 2 ]. It is routinely performed by Asians during daily life activities and farmwork [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deep squatting is a motion involving total body flexion that can be used to evaluate functional movement [ 1 , 2 ]. It is routinely performed by Asians during daily life activities and farmwork [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sitting, lifting, and other movements and postures similar to the squat are often used in daily life, and as such, the squat is often used as an exercise to improve activities of daily living. It has been reported that the squatting strategy differs between the lower back pain group and the non-lower back pain group 10) , and it is known that the load on the lumbar region varies with the squatting strategy 11,12) . During the downward phase of the squat, the extensors of the lower extremities perform eccentric contractions, and during the upward phase, the extensors of the lower extremities perform concentric contractions to control the vertical movement of the center of gravity.…”
Section: Introductionmentioning
confidence: 99%